Factors determining organic farming adoption: international research results and lessons learned for Indonesia - Ashari; Sharifuddin, Juwaidah; Mohamed, Zainal Abidin (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2017)
Indonesia is potential to develop organic farming as it has suitable land and supporting technology. Demand for organic product is supposed to increase in the future due to people’s awareness about safety and healthy food. It implies that organic farming has a good prospect to develop as agriculture-base business. However, it seems that farmers’ response to adopt organic farming technology is very low indicated by low rate of adoption. Actually, many countries have experiences in term of organic farming. This paper aims to assess determinant factors of organic farming adoption based on international research experiences and to withdraw lessons learned to raise adoption rate in Indonesia. The results showed that the determinant factors of organic farming adoption consisted of various aspects, i.e. (1) information and knowledge availability, (2) economic and financial motives, (3) technical and management skills, (4) social consideration, (5) environmental concern, (6) institutional environment, and (7) farmers’ socio-economic and demographic background. Accordingly, those aspects should be taken into account in policy formulation to encourage organic farming adoption. Indeed, government’s role is very crucial, mainly to convince farmers about organic farming benefit and to provide information as well as technical assistance.